1990
DOI: 10.1021/la00098a003
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of ruthenium catalysts prepared by the sol-gel method in reactions of benzene hydrogenation and n-pentane hydrogenolysis

Abstract: The self-poisoning of ruthenium silica catalysts has been studied for benzene hydrogenation and n-pentane hydrogenolysis. The catalysts were synthesized by the sol-gel method, which consists of adding the active metal to a sol followed by transformation to a gel. As a reference, a catalyst has been prepared by the classical impregnation method using commercial silica. In the hydrogenation of benzene, the catlysts prepared by the sol-gel method are more resistant to deactivation by carbonaceous residues. The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 1 publication
0
16
0
2
Order By: Relevance
“…The key factor in obtaining solids with different physico-chemical properties was the use of different preparative methods. It was found that when platinum based catalysts were prepared by conventional impregnation method the metal particles were easily sintered, while when using sol-gel process the catalysts had high thermal stability because the metal particles were incorporated into the framework of the support [18][19][20][21] or partially embedded in the support [22][23][24]. Embedding of metal particles in the support is well known to be effective in limiting sintering because the area of the metal-support interface is large.…”
Section: Introductionmentioning
confidence: 99%
“…The key factor in obtaining solids with different physico-chemical properties was the use of different preparative methods. It was found that when platinum based catalysts were prepared by conventional impregnation method the metal particles were easily sintered, while when using sol-gel process the catalysts had high thermal stability because the metal particles were incorporated into the framework of the support [18][19][20][21] or partially embedded in the support [22][23][24]. Embedding of metal particles in the support is well known to be effective in limiting sintering because the area of the metal-support interface is large.…”
Section: Introductionmentioning
confidence: 99%
“…By using this method, catalytic researchs have successfully prepared a variety of ultrafine particles whose catalytic properties were much better than those of large particles prepared by other methods (19)(20)(21)(22)(23). For instance, Lopez et al have used the sol-gel process to synthesize supports and metallic catalysts with high surface areas, high temperature resistance, and good catalytic properties, as well as remarkable resistance of the active metal to self-deactivation in hydrogenation reactions (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…This deactivation is caused by adsorption of dehydrogenated species on the ruthenium surface. These dehydrogenated species are formed by abstraction of hydrogen from benzene molecules [7,12]. Under the same reaction conditions the activity of an impregnation catalyst decreases more rapidly with a half-life of about 15 min [8].…”
Section: Resultsmentioning
confidence: 99%
“…Niwa et al [6] employed sol-gel manufactured ruthenium catalysts suspended in pure water and could achieve cyclohexene selectivities just as high as with impregnation catalysts in a salt containing aqueous phase. It is well-known that sol-gel catalysts are highly stable with respect to deactivation [7], so that in this work these catalysts have been used for the gas phase hydrogenation of benzene. This steady-state conversion enables, on the one hand, the investigation of kinetics and opens, on the other hand, new possibilities of reaction engineering.…”
Section: Introductionmentioning
confidence: 99%